Pengaruh Kinerja Keuangan terhadap Return Saham pada Perusahaan Farmasi di BEI Selama Masa Pandemi Covid-19 - Meilia Hasan; Jefry Gasperz; Franco Benony Limba (Financial and Accounting Indonesian Research, 2023)
This study aims to examine the effect of current ratio, debt to equity ratio and return on equity on stock returns in pharmaceutical companies listed on the indonesia stock exchange. The population in this study are pharmaceutical companies listed on the indonesia stock exchange during the covid-19 pandemic (2020-2021). The sample in this study is the financial statements of pharmaceutical companies (2020-2021) which were taken using the purposive sampling method, so that 10 companies were obtained as samples. And using multiple linear regression analysis method, classical assumption test, t test (partial test), and coefficient of determination with the help of spss (statistical product and service solutions) v16 software. Based on the results of the study, it can be concluded that partially current ratio has a positive and significant effect on stock return, while the debt to equity ratio has no significant effect on return on equity, and return on equity has a positive and significant effect on stock return in listed basic and chemical industry sector companies On the indonesia stock exchange for the period (2020-2021).